2007
DOI: 10.1128/jvi.00598-07
|View full text |Cite
|
Sign up to set email alerts
|

In Vivo and In Vitro Escape from Neutralizing Antibodies 2G12, 2F5, and 4E10

Abstract: Recently, passive immunization of human immunodeficiency virus (HIV)-

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
82
0
1

Year Published

2008
2008
2022
2022

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 85 publications
(86 citation statements)
references
References 68 publications
3
82
0
1
Order By: Relevance
“…Those studies raised concerns about the in vivo activities of 2F5 and 4E10, since the viral rebound observed in several patients occurred along with the emergence of 2G12-resistant virus, with no resistance to the MPER MAbs emerging. However, a more recent study by Manrique et al showed a different picture when they performed a more in-depth analysis of the virus in vivo and in vitro (135). No mutations in the MPER were found in virus that was obtained from patients at different time points.…”
Section: Mab 2f5 and Its Epitopementioning
confidence: 98%
“…Those studies raised concerns about the in vivo activities of 2F5 and 4E10, since the viral rebound observed in several patients occurred along with the emergence of 2G12-resistant virus, with no resistance to the MPER MAbs emerging. However, a more recent study by Manrique et al showed a different picture when they performed a more in-depth analysis of the virus in vivo and in vitro (135). No mutations in the MPER were found in virus that was obtained from patients at different time points.…”
Section: Mab 2f5 and Its Epitopementioning
confidence: 98%
“…[5][6][7]28 Second, methodological approaches for high-throughput screening and recovery of HC and LC genes from individual patient B cells did not exist until more recently, and the previously identified bNAbs were not potent enough to prevent viral escape, even when delivered in combination. [29][30][31][32] Compared with the current crop of bNAbs, first-generation bNAbs have much reduced binding affinities and higher IC 50 values, likely insufficient to be used prophylactically or therapeutically in humans.…”
Section: Discussionmentioning
confidence: 99%
“…[54][55][56][57][58][59][60] Among these nAbs, 2G12, 2F5 and 4E10 are three of the most broadly used Abs cloned from HIV-1-infected patients. 54,55,57,58,[61][62][63][64] 2G12 recognizes a unique mannosedependent epitope within gp120, 55,61,[65][66][67] while binding sites of 2F5 and 4E10 lie within a well-defined region of the membrane-proximal external region of gp41. 54,57,58,60,68 Passive immunization with a cocktail of these three human monoclonal Abs was effective in animal models, i.e., it conferred protection against intravenous, intravaginal or oral challenge with simian human immunodeficiency virus (a monkey HIV-1 analog) in rhesus macaques.…”
Section: Protective Role Of Complement Activation and Ab Immunity In mentioning
confidence: 99%
“…[69][70][71] However, in a clinical trials with this nAb cocktail in six acutely and eight chronically HIV-1-infected individuals undergoing interruption of HAART, only two of eight chronically infected individuals showed evidence of a delay in viral rebound during the passive immunization, indicating the limits of these nAbs in controlling HIV-1 infection. 64,72 Why does passive immunization with a cocktail of nAbs provide anti-HIV-1 protection in animal models, but not in humans? Did the HIV-1 viruses mutate under the Ab immune pressure in humans?…”
Section: Protective Role Of Complement Activation and Ab Immunity In mentioning
confidence: 99%